Leading Digital Transformation: Strategies for Higher Education Leaders in Navigating Online Platforms, Administrative Services, and Cybersecurity - Yuli Evitha (STAI Hubbulwathan Duri, 2024)
This systematic literature review (SLR) investigates strategies for higher education leaders to successfully navigate digital transformation, concentrating on online platforms, administrative services, and cybersecurity, with a focus on publications from 2015 to 2023. Data sources for this review include Google Scholar, PubMed, IEEE Xplore, and ERIC. A total of 25 studies were selected based on inclusion criteria that prioritized relevance, recency, and methodological rigor. The review synthesizes findings from these diverse sources to pinpoint best practices and innovative methods for managing digital changes within academic institutions. Key themes identified include the implementation of robust cybersecurity measures, such as multifactor authentication and regular security audits; the optimization of online learning environments through adaptive learning technologies; and the enhancement of administrative efficiencies via automated processes and data analytics. Additionally, the study explores challenges encountered by educational leaders, such as resistance to change, budget constraints, and the necessity for continuous professional development, detailing how these factors impede or facilitate digital transformation. The review concludes by emphasizing the pivotal role of strategic leadership in fostering a culture of innovation and resilience in higher education. Effective leadership strategies highlighted include proactive change management, strategic allocation of resources, and ongoing investment in staff training. By adopting these approaches, institutions can better adapt to evolving technological landscapes and meet the demands of contemporary students and staff.